Positive electrode material and preparation method and application thereof
By using Sn and Zn in situ double-doped O3 and P2 positive electrode materials in sodium ion battery positive electrode materials, the P2/O3 mixed phase single crystal positive electrode material is formed, which solves the irreversible phase change and poor storage stability under high pressure. The problem is that electrochemical properties with high energy density and long cycle life are achieved.
Patent Information
- Application Number
- CN202411616346.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-13
AI Technical Summary
The existing sodium ion battery positive electrode materials have problems such as irreversible phase change, poor storage stability, and unstable interface under high voltage, and it is difficult to improve energy density and cycle stability at high voltages at the same time.
The combination of O3 and P2 positive electrode materials with in-situ double-doped Sn and Zn is used to form a P2/O3 mixed single crystal positive electrode material. By adjusting the material proportion and doping amount, the structure and electrochemical properties of the material are optimized.
Effectively shortens the irreversible phase change zone of the high voltage platform, improves the high capacity and average voltage of the material at a high voltage of 4.2V, enhances the stability and high rate performance of electrochemical performance, and combines high energy density and structure. stability.
Smart Images

Figure CN119447278A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of positive electrode materials, and specifically relates to a mixed-phase high-voltage sodium ion battery positive electrode material with a P2 / O3 mixed-phase structure, and a preparation method and application thereof. Background Art
[0002] O3-type layered Na x TMO2 cathode materials have disadvantages such as irreversible phase change, poor storage stability, and unstable interface. In order to improve the structure and storage stability of layered cathodes through cation substitution technology, researchers have made many attempts, such as using Zn 2+ , Fe 3+ Cr 3+ 、Ti 4+ 、V 5+ The main element doping and substitution are carried out, which is one of the differences from the positive electrode materials of lithium-ion batteries. Multiple elements show electrochemical activity and reversibility. The cation substitution in the transition metal layer can effectively inhibit the irreversible phase change, thereby improving the structural stability, air stability and electrochemical performance of the positive electrode material.
[0003] However, the current study of Na x The charge cut-off voltage of TMO2 is generally ≤4.0V, which is a great disadvantage compared with lithium-ion batteries in terms of energy density, and its substitution mechanism under high voltage is not fully understood. It is of great significance to design and develop an O3-type layered material with good high-voltage storage stability and high-voltage cycling performance.
[0004] The lower standard electrochemical potential of sodium ion electrode materials determines that they must operate at higher voltages to pursue energy density equivalent to that of lithium materials; however, at high pressures, complex phase transitions and severe interfacial reactions inevitably reduce their service life. This inherent contradiction makes it extremely difficult to develop sodium-containing layered oxide materials with both high energy density and long cycle life. While P2-type layered materials not only have strong resistance to hygroscopic degradation, but can also maintain their original structure over a wider voltage range, thus exhibiting high cycle performance, but due to insufficient sodium content and electrochemical dissolution of the material during discharge, resulting in low energy density, people have been committed to modifying the structure to overcome the shortcomings of each material. The strategy is to develop small strain materials with smooth charge and discharge curves and uniform sodium ion distribution. The smooth charge and discharge curves indicate stable solid solution reactions. Stabilizing, inhibiting this high-pressure phase transition and extending the solid solution zone are essential to further improve the structural stability of layered sodium oxide materials at high charge cutoff voltages. Therefore, people are committed to designing dual-phase O3 and P2-type material structures to make up for the shortcomings of the two pure phases.
[0005] CN114678523A discloses a novel biphasic layered sodium-ion battery cathode material with the general formula NaxM1-y-zMnyTizO2. In this general formula, M includes at least one of iron, zinc, nickel, magnesium, lithium, cobalt, chromium, vanadium, titanium, and aluminum, and 0.5 ≤ x ≤ 1.0, 0 < y ≤ 1.0, 0 < z ≤ 1.0. Appropriate Ti doping promotes the formation of the O3 phase, and the two-phase ratio of P2 and O3 phases can be further adjusted by regulating the doping ratio of Ti. Under the synergistic effect of the P2 / O3 biphasic structure, the P2→O2 phase transition at a high voltage of 4.3V can be effectively inhibited, and the volume change can be effectively alleviated. Therefore, a stable P2 / O3 phase structure is maintained, and the stability of Na+ insertion and extraction is ensured, thereby achieving higher cycle stability. The cathode material prepared by the present invention has a high energy density, rate performance, and good cycle performance. However, the molar ratio of Ni in the raw materials of this material is 0.35 - 0.4, which偏向 the nickel-increasing route in the development of oxide cathodes (0 < Ni ≤ 0.33). One of the reasons for its high capacity and excellent cycle performance may be the contribution of high nickel and high titanium (the molar ratio of Ti in Example 2 is 0.2), and at the same time, extra NiO impurity peaks will appear in the characterization; secondly, the carbonate used as the manganese source will generate more CO2 during the sintering process compared with the manganese oxide source, and even more gas will be generated inevitably during the subsequent battery cycling process, so there is a lack of subsequent tail gas treatment measures; thirdly, this document does not mention the shortening of the phase transition platform during the charging process of this material. Summary of the Invention
[0006] The purpose of the present invention is to provide a mixed-phase high-voltage sodium-ion battery layered cathode material, its preparation method and application. This cathode material has both a high energy density, a short high-voltage phase transition region, high cycle performance, and structural stability.
[0007] To achieve the above purpose, the present invention adopts the following technical solutions: In the first aspect, the present invention provides a sodium-ion battery cathode material, including the following components: O3-type cathode material and P2-type cathode material; The O3-type cathode material is Na n Ni x Zn y Fe 1 / 3 Mn 1 / 3 O2, where 0.95 ≤ n ≤ 1.02, 0 < x ≤ 0.33, x + y = 0.33; The P2-type cathode material is Na m Ni p Mn q Mg z Ti 1-p-q-zO2, where 0.67≤m≤0.8, 0<p≤0.25, 0.33<q≤0.6, 0.01<z≤0.05; The mass ratio of the O3 type positive electrode material to the P2 type positive electrode material is 1:(0.3-3).
[0008] The present invention combines an O3-type positive electrode material and a P2-type positive electrode material that are in situ doped with two active elements (Zn and Sn) to form a P2 / O3 mixed-phase single-crystalline positive electrode material, thereby improving the stability of the electrochemical performance and the high-rate performance of the positive electrode material, and solving the problems of existing sodium-ion battery positive electrode materials, namely, maintaining the structural stability of the single-crystalline material, solving the existing capacity and voltage platforms, and shortening the high-voltage phase change zone.
[0009] According to a specific embodiment of the present invention, the mass ratio of the O3 type positive electrode material to the P2 type positive electrode material is 3:1.
[0010] According to a specific embodiment of the present invention, the O3 type positive electrode material is NaNi doped with Sn and Zn in situ. 0.33 Fe 0.33 Mn 0.33 O2.
[0011] According to a specific embodiment of the present invention, the P2 type positive electrode material is Na 0.67 Ni 0.25 Mn 0.6 Mg 0.033 Ti 0.117 O2.
[0012] In a second aspect, the present invention provides a method for preparing the above-mentioned sodium ion battery positive electrode material, comprising the following steps: S1, mixing a sodium source, a nickel source, an iron source, a manganese source, a zinc source and a tin source, and calcining them to obtain an O3 type positive electrode material; S2, mixing a sodium source, a nickel source, a manganese source, a magnesium source and a titanium source, and calcining them to obtain a P2 type positive electrode material; S3, mixing the O3 type positive electrode material with the P2 type positive electrode material to obtain a mixed-phase P2 / O3 type positive electrode material.
[0013] In the above preparation method, in step S1, the mixing is performed according to any of the following conditions: 1) Mixing sodium source, nickel source, iron source and manganese source, and then doping with zinc source and tin source; 2) Mix the sodium source, nickel source, iron source, manganese source and tin source, and then dope the zinc source.
[0014] In the above preparation method, in step S1, the sodium source is selected from anhydrous sodium carbonate.
[0015] In the above preparation method, in step S1, the nickel source is selected from nickel oxide.
[0016] In the above preparation method, in step S1, the iron source is selected from ferric oxide.
[0017] In the above preparation method, in step S1, the manganese source is selected from one or more of trimanganese tetraoxide, manganese dioxide and manganese oxide.
[0018] In the above preparation method, in step S1, the zinc source is selected from zinc oxide.
[0019] In the above preparation method, in step S1, the tin source is selected from tin dioxide.
[0020] In the above preparation method, in step S1, the calcination conditions are: temperature of 900-1000° C., preferably 950° C., and time of 10-20 h.
[0021] In the above preparation method, in step S1, the calcination is carried out according to the following operation: first heating to 450-550°C (preferably 500°C), keeping warm for 3-7h (preferably 5h), continuing to heat to 900-1000°C (preferably 950°C), keeping warm for 12-18h (preferably 15h), and the heating rate is 2°C / min; then cooling to 600-700°C (preferably 650°C), keeping warm for 0.5-3.5h (preferably 2h), and the cooling rate is 2°C / min.
[0022] In the above preparation method, in step S2, the sodium source is selected from anhydrous sodium carbonate.
[0023] In the above preparation method, in step S2, the nickel source is selected from nickel oxide.
[0024] In the above preparation method, in step S2, the manganese source is selected from one or more of trimanganese tetraoxide, manganese dioxide and manganese oxide.
[0025] In the above preparation method, in step S2, the magnesium source is selected from magnesium oxide.
[0026] In the above preparation method, in step S2, the titanium source is selected from titanium dioxide.
[0027] In the above preparation method, in step S2, the calcination conditions are: temperature of 850-950°C, preferably 900°C, and time of 12-18h; In the above preparation method, in step S2, the calcination is carried out according to the following operation: first, the temperature is raised to 450-550°C (preferably 500°C), kept warm for 3-7h (preferably 5h), and then the temperature is raised to 850-950°C (preferably 900°C), kept warm for 12-18h (preferably 15h), and the heating rate is 2°C / min; then the temperature is lowered to 600-700°C (preferably 650°C), kept warm for 0.5-3.5h (preferably 2h), and the cooling rate is 2°C / min.
[0028] In a third aspect, the present invention provides a sodium ion battery comprising a positive electrode and a negative electrode; the material of the positive electrode comprises the above-mentioned positive electrode material.
[0029] Compared with the prior art, the present invention has the following beneficial effects: The high-voltage P2 / O3 mixed-phase sodium ion battery positive electrode material provided by the present invention can effectively shorten the high-voltage platform that produces irreversible phase change, and improve the average voltage while ensuring high capacity at a high voltage of 4.2V, thereby improving the stability of the electrochemical performance of the positive electrode material and the high-rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is the 2-4.2V high voltage platform variation curve in the first charging curve of the embodiment and the comparative example.
[0031] Figure 2 It is the XRD characterization diagram of different proportions of O3 and P2 phase materials in the embodiment.
[0032] Figure 3 This is a scanning electron microscope image of the mixed-phase positive electrode material synthesized in Example 1. DETAILED DESCRIPTION
[0033] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments.
[0034] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0035] Unless otherwise specified, the reagents, materials, instruments, etc. used in the following examples can be obtained from commercial sources.
[0036] Example 1: Sn and Zn in-situ doped O3-type and P2-type mixed-phase positive electrode material (1) Preparation of O3 type positive electrode materials: The mass of sodium carbonate is calculated based on the total material concentration of 2 mol and the sodium content of 1 mol; the mass of nickel oxide, ferric oxide, and manganese tetraoxide are calculated according to the molar ratio of 1:1:1 for the nickel source, iron source, and manganese source, respectively; 5000 ppm zinc oxide and 2000 ppm tin dioxide are weighed as auxiliary materials based on the total material, and each raw material is weighed and transferred to a ball mill and placed in a 3D mixer for mixing for 3 hours; The mixed material was taken out and transferred to a muffle furnace. The temperature program was set as follows: 0-500°C heating, heating rate of 2°C / min, heat preservation for 5 hours; 500-950°C heating, heating rate of 2°C / min, heat preservation for 15 hours; 950-650°C cooling, cooling rate of 2°C / min, heat preservation for 2 hours; after cooling to room temperature, the sintered material was taken out for crushing, and sieved under a 250-mesh sieve to obtain Sn and Zn in-situ doped O3-type NaNi 0.33 Fe 0.33 Mn 0.33 O2.
[0037] (2) Preparation of P2 type positive electrode material: The mass of sodium carbonate was calculated based on the total material concentration of 2 mol, the amount of sodium added was 0.67 mol and the excess was 5%; the mass of nickel oxide, manganese tetraoxide, magnesium oxide and titanium dioxide were calculated based on the molar ratio of 0.25:0.6:0.033:0.117 for the nickel source, manganese source, magnesium source and titanium source, respectively. After weighing each raw material, transfer it to a ball mill and put it into a 3D mixer for mixing for 3 hours; The mixed material was taken out and transferred to a muffle furnace. The temperature program was set as follows: 0-500°C heating, heating rate of 2°C / min, heat preservation for 5h; 500-900°C heating, heating rate of 2°C / min, heat preservation for 15h; 900-650°C cooling, cooling rate of 2°C / min, heat preservation for 2h; high-temperature calcination in air was performed, and after cooling to room temperature, the sintered material was taken out for crushing and sieved under a 250-mesh sieve to obtain a P2-type positive electrode material Na 0.67 Ni 0.25 Mn 0.6 Mg 0.033 Ti 0.117 O2.
[0038] (3) Mixing: The O3 type positive electrode material obtained in step (1) and the P2 type positive electrode material obtained in step (2) are weighed in a molar ratio of 3:1, placed in a sealed can, and transferred to a 3D mixer for mixing for 3 hours to obtain a mixed-phase positive electrode material.
[0039] Example 2: Sn and Zn in-situ doped O3-type and P2-type mixed-phase positive electrode material (1) Preparation of O3 type positive electrode materials: The mass of sodium carbonate was calculated based on the total material concentration of 2 mol and the amount of sodium added of 1 mol. The masses of nickel oxide, ferric oxide, manganese tetraoxide and tin dioxide were calculated according to the molar ratio of 0.33:0.33:0.3:0.03 for the nickel source, iron source, manganese source and tin source, respectively. The auxiliary material 5000 ppm zinc oxide was calculated and weighed based on the total material. After weighing each raw material, it was transferred to a ball mill and placed in a 3D mixer for mixing for 3 hours.
[0040] The mixed material was taken out and transferred to a muffle furnace. The temperature program was set as follows: 0-500°C heating, heating rate of 2°C / min, heat preservation for 5h; 500-950°C heating, heating rate of 2°C / min, heat preservation for 15h; 950-650°C cooling, cooling rate of 2°C / min, heat preservation for 2h; high-temperature calcination in air was performed, and after cooling to room temperature, the sintered material was taken out for crushing and sieved under a 250-mesh sieve to obtain Sn and Zn in-situ doped O3-type NaNi 0.33 Fe 0.33 Mn 0.33 O2.
[0041] (2) Preparation of P2 type positive electrode material: The mass of sodium carbonate was calculated based on the total material concentration of 2 mol, the amount of sodium added was 0.67 mol and the excess was 5%; the mass of nickel oxide, manganese tetraoxide, magnesium oxide and titanium dioxide were calculated based on the molar ratio of 0.25:0.6:0.033:0.117 for the nickel source, manganese source, magnesium source and titanium source, respectively. After weighing each raw material, transfer it to a ball mill and put it into a 3D mixer for mixing for 3 hours; The mixed material was taken out and transferred to a muffle furnace. The temperature program was set as follows: 0-500°C heating, heating rate of 2°C / min, heat preservation for 5h; 500-900°C heating, heating rate of 2°C / min, heat preservation for 15h; 900-650°C cooling, cooling rate of 2°C / min, heat preservation for 2h; high-temperature calcination in air was performed, and after cooling to room temperature, the sintered material was taken out for crushing and sieved under a 250-mesh sieve to obtain a P2-type positive electrode material Na 0.67 Ni 0.25 Mn 0.6 Mg 0.033 Ti 0.117 O2.
[0042] (3) Mixing: The above-mentioned O3 type positive electrode material and P2 type positive electrode material are weighed in a molar ratio of 3:1, placed in a sealed can and transferred to a 3D mixer for mixing for 3 hours to obtain a mixed-phase positive electrode material.
[0043] Comparative Example 1: Sn and Zn in-situ doped O3 type positive electrode material The mass of sodium carbonate was calculated based on the total material concentration of 2 mol and the amount of sodium added of 1 mol. The masses of nickel oxide, ferric oxide, and manganese oxide were calculated according to the molar ratio of 1:1:1 for the nickel source, iron source, and manganese source, respectively. According to the total material, 5000 ppm zinc oxide and 2000 ppm tin dioxide were calculated and weighed as auxiliary materials. After weighing each raw material, transfer it to a ball mill and put it into a 3D mixer for mixing for 3 hours.
[0044] The mixed material was taken out and transferred to a muffle furnace. The temperature program was set as follows: 0-500°C heating, heating rate of 2°C / min, heat preservation for 5h; 500-950°C heating, heating rate of 2°C / min, heat preservation for 15h; 950-650°C cooling, cooling rate of 2°C / min, heat preservation for 2h; high-temperature calcination in air was performed, and after cooling to room temperature, the sintered material was taken out for crushing and sieved under a 250-mesh sieve to obtain Sn and Zn in-situ doped O3-type NaNi 0.33 Fe 0.33 Mn 0.33 O2.
[0045] Comparative Example 2: P2 type positive electrode material The mass of sodium carbonate was calculated based on the total material concentration of 2 mol, the amount of sodium added was 0.67 mol and the excess was 5%; the mass of nickel oxide, manganese tetraoxide, magnesium oxide and titanium dioxide were calculated based on the molar ratio of 0.25:0.6:0.033:0.117 for the nickel source, manganese source, magnesium source and titanium source, respectively. After weighing each raw material, transfer it to a ball mill and put it into a 3D mixer for mixing for 3 hours; The mixed material was taken out and transferred to a muffle furnace. The temperature program was set as follows: 0-500°C heating, heating rate of 2°C / min, heat preservation for 5h; 500-900°C heating, heating rate of 2°C / min, heat preservation for 15h; 900-650°C cooling, cooling rate of 2°C / min, heat preservation for 2h; high-temperature calcination in air was performed, and after cooling to room temperature, the sintered material was taken out for crushing and sieved under a 250-mesh sieve to obtain a P2-type positive electrode material Na 0.67 Ni 0.25 Mn 0.6 Mg 0.033 Ti 0.117 O2.
[0046] Comparative Example 3: Sn and Zn in-situ doped O3 type positive electrode material [O3 type, doped with Zn, Sn replacing part of Mn] The mass of sodium carbonate was calculated based on the total material concentration of 2 mol and the amount of sodium added of 1 mol. The masses of nickel oxide, ferric oxide, manganese tetraoxide and tin dioxide were calculated according to the molar ratio of 0.33:0.33:0.3:0.03 for the nickel source, iron source, manganese source and tin source, respectively. The auxiliary material 5000 ppm zinc oxide was calculated and weighed based on the total material. After weighing each raw material, it was transferred to a ball mill and placed in a 3D mixer for mixing for 3 hours.
[0047] The mixed material was taken out and transferred to a muffle furnace. The temperature program was set as follows: 0-500°C heating, heating rate of 2°C / min, heat preservation for 5h; 500-950°C heating, heating rate of 2°C / min, heat preservation for 15h; 950-650°C cooling, cooling rate of 2°C / min, heat preservation for 2h; high-temperature calcination in air was performed, and after cooling to room temperature, the sintered material was taken out for crushing and sieved under a 250-mesh sieve to obtain Sn and Zn in-situ doped O3-type NaNi 0.33 Fe 0.33 Mn 0.33 O2.
[0048] Test Case The positive electrode materials obtained in Example 1, Example 2, Comparative Example 1, Comparative Example 2, and Comparative Example 3 are made into buckle batteries, and the specific steps are as follows: The positive electrode materials obtained in Example 1, Example 2, Comparative Example 1, Comparative Example 2, and Comparative Example 3 were respectively mixed with a conductive agent sp and a binder PVDF in a mass ratio of 9:0.5:0.5 to prepare a slurry; Slurry mixing steps: ① Take 4g of PVDF glue in a clean and dry slurry mixing tank, add 0.2g of SP, and put it into the slurry mixing machine for the first slurry mixing; ② After the first slurry mixing, weigh 3.6g of active substance and 2.5g of NMP and add them into the slurry mixing tank for the second slurry mixing; The slurry was then coated on an aluminum foil current collector with a coating thickness of 400 μm. After drying, rolling, and vacuum drying at 80 ° C for 12 h, a positive electrode for a sodium ion battery was obtained. The compaction density of the electrode was controlled to be about 2.5 g / cm 3 , get the power off.
[0049] Set the prepared button battery to the 2.0-4.2V test step for capacity and voltage platform testing.
[0050] The results are as follows.
[0051] 1. Electrochemical performance Table 1 Electrochemical performance of Examples 1-2 and Comparative Examples 1-3
[0052] As can be seen from Table 1, the 4.2V capacity of the positive electrode materials obtained in Example 1 and Example 2 can reach about 150mAh / g, and the first efficiency reaches more than 93.7%, which is slightly lower than the pure O3 type positive electrode materials in Comparative Examples 1 and 3, but the average voltage is higher than that in Comparative Examples 1 and 3, which is increased by 0.034V; the first efficiency of the pure P2 type positive electrode material in Comparative Example 2 is higher, but the 4.2V capacity is too low, only 95.7mAh / g; the capacity and rate performance of the positive electrode material in Comparative Example 3 are lower than those in Comparative Example 1.
[0053] 2. High-voltage phase change zone from Figure 1 It can be clearly seen that the high-voltage phase change zone of the mixed-phase positive electrode material obtained in Example 1 and Example 2 is significantly shortened, which shows that whether as a doping element or as a main element replacing part of the manganese source, the dual doping of Sn and Zn can shorten the phase change zone and increase the solid solution zone.
[0054] The charging curve of the pure O3 type positive electrode material obtained in Comparative Example 1 has a very obvious high-voltage phase change zone; the charging and discharging curve of the pure P2 type positive electrode material obtained in Comparative Example 2 is very smooth, indicating that its solid solution zone is very stable; the charging curve trends of Comparative Example 3 and Comparative Example 1 in the high voltage range are the same, but the capacity is lower.
[0055] 3. Microstructure The O3 type positive electrode material and the P2 type positive electrode material in Example 1 were mixed at a ratio of 1:1 and 1:3 respectively to obtain mixed-phase positive electrode materials with different mixing ratios. The structures of the mixed-phase positive electrode materials were characterized by XRD.
[0056] The results are as follows Figure 2 As shown. Figure 2 It can be seen that the mixed-phase cathode materials obtained with different mixing ratios still maintain a strong O3-type characteristic peak, indicating that their structure has not been changed by the doping of the P2-type cathode material.
[0057] from Figure 3 It can be seen that the microscopic morphology of the mixed-phase positive electrode material obtained in Example 1 is obvious single crystal particles.
[0058] The above test results show that the present invention can effectively shorten the high voltage platform that produces irreversible phase change by double doping with Sn and Zn, and improve the average voltage while ensuring high capacity at a high voltage of 4.2V, thereby improving the stability of the electrochemical performance and high rate performance of the positive electrode material. The obtained high voltage P2 / O3 mixed phase sodium ion battery positive electrode material has high energy density, short high voltage phase change zone, high cycle performance and structural stability.
[0059] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. A sodium ion battery positive electrode material, comprising the following components: an O3 type positive electrode material and a P2 type positive electrode material; The O3 type positive electrode material is Na2O3 doped with Sn and Zn in situ. n Ni x Zn y Fe 1 / 3 Mn 1 / 3 O2, where 0.95≤n≤1.02, 0<x≤0.33, x+y=0.33; The P2 type positive electrode material is Na m Ni p Mn q Mg z Ti 1-p-q-z O2, where 0.67≤m≤0.8, 0<p≤0.25, 0.33<q≤0.6, 0.01<z≤0.05; The mass ratio of the O3 type positive electrode material to the P2 type positive electrode material is 1:(0.3-3).
2. The sodium ion battery positive electrode material according to claim 1, characterized in that The mass ratio of the O3 type positive electrode material to the P2 type positive electrode material is 3:
1.
3. The sodium ion battery positive electrode material according to claim 1 or 2, characterized in that The O3 type positive electrode material is NaNi doped with Sn and Zn in situ 0.33 Fe 0.33 Mn 0.33 O2; The P2 type positive electrode material is Na 0.67 Ni 0.25 Mn 0.6 Mg 0.033 Ti 0.117 O2.
4. The method for preparing the positive electrode material for a sodium ion battery according to any one of claims 1 to 3, comprising the following steps: S1, mixing a sodium source, a nickel source, an iron source, a manganese source, a zinc source and a tin source, and calcining them to obtain an O3 type positive electrode material; S2, mixing a sodium source, a nickel source, a manganese source, a magnesium source and a titanium source, and calcining them to obtain a P2 type positive electrode material; S3, mixing the O3 type positive electrode material with the P2 type positive electrode material to obtain a mixed-phase P2 / O3 type positive electrode material.
5. The preparation method according to claim 4, characterized in that: In step S1, the mixing is performed according to any of the following conditions: 1) Mixing sodium source, nickel source, iron source and manganese source, and then doping with zinc source and tin source; 2) Mix the sodium source, nickel source, iron source, manganese source and tin source, and then dope the zinc source.
6. The preparation method according to claim 4 or 5, characterized in that: In step S1, the sodium source is selected from anhydrous sodium carbonate; The nickel source is selected from nickel oxide; The iron source is selected from ferric oxide; The manganese source is selected from one or more of trimanganese tetraoxide, manganese dioxide and manganese oxide; The zinc source is selected from zinc oxide; The tin source is selected from tin dioxide.
7. The preparation method according to any one of claims 4 to 6, characterized in that: In step S1, the calcination conditions are: temperature of 900-1000°C and time of 15h; The calcination is carried out according to the following operation: firstly heating to 450-550°C, keeping the temperature for 3-7h, then heating to 900-1000°C, keeping the temperature for 12-18h, and the heating rate is 2°C / min; then cooling to 600-700°C, keeping the temperature for 0.5-3.5h, and the cooling rate is 2°C / min.
8. The preparation method according to any one of claims 4 to 7, characterized in that: In step S2, the sodium source is selected from anhydrous sodium carbonate; The nickel source is selected from nickel oxide; The manganese source is selected from one or more of trimanganese tetraoxide, manganese dioxide and manganese oxide; The magnesium source is selected from magnesium oxide; The titanium source is selected from titanium dioxide.
9. The preparation method according to any one of claims 4 to 8, characterized in that: In step S2, the calcination conditions are: temperature of 850-950°C and time of 15h; The calcination is carried out according to the following operation: firstly heating to 450-550°C, keeping the temperature for 3-7h, then heating to 850-950°C, keeping the temperature for 12-18h, and the heating rate is 2°C / min; then cooling to 600-700°C, keeping the temperature for 0.5h-3.5h, and the cooling rate is 2°C / min.
10. A sodium ion battery comprising a positive electrode and a negative electrode; the material of the positive electrode comprises the positive electrode material according to any one of claims 1 to 3.
Citation Information
Patent Citations
Novel double-phase layered sodium ion battery positive electrode material
CN114678523A
Double-function coating method for layered positive electrode material of sodium-ion battery and application of double-function coating method
CN117613238A
Sodium ion layered metal oxide material, preparation method thereof, positive electrode material and sodium ion battery
CN117747834A
P2 and P3 mixed phase layered oxide sodium-ion battery positive electrode material as well as preparation method and application thereof
CN118136830A
Layered oxide sodium-ion battery positive electrode material with P2 / O3 biphase symbiotic structure as well as preparation method and application of layered oxide sodium-ion battery positive electrode material
CN118867228A
Cited By
High-transmission wide-temperature-range sodium-ion battery positive electrode based on biphase layered oxide as well as preparation method and application of high-transmission wide-temperature-range sodium-ion battery positive electrode
CN122091557A
Positive electrode material preparation method therefor, and use thereof
WO2026103585A1